Quantum dot glue as well as preparation method and application thereof
By using phosphoricate polymers and sulfur -containing acrylics such as sulfur -containing acrylics in quantum dot glue, and using UTG tablets packaging methods to solve the problem of performance attenuation and insufficient high temperature resistance in quantum dot glue during application. Realize high-stability, good opticality and low-cost UTG-QD board.
Patent Information
- Application Number
- CN202310882521.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-18
- Publication Date
- 2025-01-28
AI Technical Summary
Existing quantum dispenser is susceptible to oxygen and water when used, resulting in reduced performance attenuation and quantum photoconversion, and high packaging method, poor stability and insufficient high temperature resistance.
Use quantum dot glue with components such as phosphate polymer and sulfur -containing acrylics, and improve the optical conversion rate of quantum dots through compatibility and stability of these components, and improve the resistance of glue through the packaging of UTG tablets. High temperature and cost benefits.
The high stability and good optical nature of quantum dot glue are realized, and the optical conversion rate and high temperature stability of the UTG-QD board are improved, and the cost is reduced.
Smart Images

Figure BDA0004353635170000021 
Figure BDA0004353635170000061 
Figure BDA0004353635170000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of quantum dots and relates to quantum dot glue and a preparation method and application thereof. Background Art
[0002] Quantum dots are a quasi-zero-dimensional nanomaterial. Quantum dots have the advantages of easy adjustment of fluorescence emission peak and narrow emission half-peak width. Currently, quantum dots are widely used in the field of backlight display and lighting. When used, quantum dots are easily affected by oxygen and water in the environment, causing performance degradation and lowering the quantum light conversion rate of quantum dots.
[0003] At present, the packaging method used for quantum dots to block oxygen and water is: the upper and lower layers of PET are used to encapsulate the quantum dot glue to form a QDEF film. The QDEF film has the advantages of high transparency, high mechanical strength, high conductivity, and strong controllability. Although the QDEF film has many advantages, it also has some disadvantages: high cost and poor stability. The poor high temperature resistance caused by the use of PET plastic film for packaging limits the application of the QDEF film.
[0004] Therefore, it is desirable in the art to develop a quantum dot glue having good stability. When the quantum dot glue is prepared into a brightness enhancement sheet, the brightness enhancement sheet has good optical properties, high temperature resistance, and low cost. Summary of the invention
[0005] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a quantum dot glue and a preparation method and application thereof. In the quantum dot glue provided by the present invention, the red quantum dots and the green quantum dots have good compatibility with other components in the glue, thereby reducing the adverse effects on the quantum dot light conversion rate. After the quantum dot glue is prepared into a light conversion element UTG-QD board, the quantum dots can still maintain a relatively high quantum dot light conversion rate.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a quantum dot glue, wherein the raw materials for preparing the quantum dot glue include the following components in parts by weight:
[0008]
[0009] In the present invention, the phosphate-containing polymer can be used as a surface ligand to protect quantum dots and increase their stability, and can also be used as a potting material to encapsulate quantum dots; the thiol-containing acrylic monomer is used as a diluent, which has good compatibility with red and green quantum dots and prevents quantum dots from quenching. When the quantum dot glue is used for a UTG-QD board, the light conversion rate of the UTG-QD board can be increased.
[0010] In the present invention, the raw materials for preparing the quantum dot glue are calculated by weight, and the amount of the phosphate ester polymer used can be 20 parts, 23 parts, 25 parts, 28 parts, 30 parts, 33 parts, 35 parts, 38 parts, 40 parts, 43 parts, 45 parts, 48 parts or 50 parts, etc.
[0011] In the present invention, the raw materials for preparing the quantum dot glue are measured in parts by weight, and the amount of the thiol-containing acrylic monomer can be 10 parts, 13 parts, 15 parts, 18 parts, 20 parts, 23 parts, 25 parts, 28 parts, 30 parts, 33 parts, 35 parts, 38 parts, 40 parts or 42 parts.
[0012] In the present invention, the raw materials for preparing the quantum dot glue are measured by weight, and the amount of the heat stabilizer can be 10 parts, 13 parts, 15 parts, 18 parts, 20 parts, 23 parts, 25 parts, 28 parts or 30 parts.
[0013] In the present invention, the raw materials for preparing the quantum dot glue are measured in parts by weight, and the amount of the photoinitiator used can be 0.5 parts, 0.8 parts, 1 parts, 2 parts, 3 parts, 4 parts or 5 parts.
[0014] In the present invention, the raw materials for preparing the quantum dot glue are measured by weight, and the amount of the light stabilizer used can be 0.1 part, 0.2 part, 0.3 part, 0.4 part or 0.5 part, etc.
[0015] In the present invention, the raw materials for preparing the quantum dot glue are measured in parts by weight, and the amount of the defoaming agent used can be 0.1 part, 0.2 part, 0.3 part, 0.4 part, 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part or 1 part, etc.
[0016] In the present invention, the raw materials for preparing the quantum dot glue are calculated by weight, and the amount of red quantum dots used can be 1 part, 1.1 parts, 1.2 parts or 1.3 parts, etc.
[0017] In the present invention, the raw materials for preparing the quantum dot glue are measured in parts by weight, and the amount of green quantum dots used can be 0.1 parts, 0.11 parts, 0.12 parts, 0.13 parts, 0.14 parts or 0.15 parts, etc.
[0018] In the present invention, the raw materials for preparing the quantum dot glue are calculated by weight, and the amount of titanium dioxide used can be 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts or 1 parts.
[0019] Preferably, the phosphoric acid ester polymer comprises BASF PA9083 resin and / or WDS-9051 phosphoric acid ester resin.
[0020] Preferably, the thiol-containing acrylic monomer includes any one or a combination of at least two of methyl 3-mercaptoacrylate, ethyl 3-mercaptoacrylate, ethylene glycol di(3-mercaptopropionate), trimethylolpropane tris(3-mercaptopropionate) or pentaerythritol tetrakis(3-mercaptopropionate).
[0021] Preferably, the thermal stabilizer comprises tricyclodecane dimethanol diacrylate.
[0022] Preferably, the photoinitiator comprises 1-hydroxycyclohexyl phenyl ketone.
[0023] Preferably, the light stabilizer comprises BASF Tinuvin 249.
[0024] Preferably, the defoaming agent comprises KS Chemical Rheoflow LP-2745.
[0025] Preferably, the red quantum dots are CdS / ZnS, and the surface ligands of the red quantum dots are oleic acid (ie, C18 carboxylic acid) or octanethiol (C8 thiol).
[0026] Preferably, the green quantum dots are CdS / ZnS, and the surface ligands of the red quantum dots are oleic acid or octanethiol.
[0027] In a second aspect, the present invention provides a method for preparing the quantum dot glue as described in the first aspect, the preparation method comprising the following steps:
[0028] (1) mixing a thiol-containing acrylic monomer, a heat stabilizer, a photoinitiator, and a light stabilizer to obtain a first mixture;
[0029] (2) adding the phosphoric acid ester polymer to the first mixture and mixing to obtain a second mixture;
[0030] (3) adding green quantum dots to the second mixture and mixing to obtain a third mixture;
[0031] (4) adding red quantum dots to the third mixture and mixing to obtain a fourth mixture;
[0032] (5) Add titanium dioxide and a defoaming agent to the fourth mixture and mix them to obtain the quantum dot glue.
[0033] Preferably, the mixing speed in step (1) is 200-400 rpm, such as 200 rpm, 250 rpm, 300 rpm, 350 rpm or 400 rpm, and the mixing time is 20-40 minutes, such as 20 minutes, 25 minutes, 30 minutes, 35 minutes or 40 minutes, etc.
[0034] Preferably, the mixing speed in step (2) is 200-400 rpm, such as 200 rpm, 250 rpm, 300 rpm, 350 rpm or 400 rpm, and the mixing time is 20-40 minutes, such as 20 minutes, 25 minutes, 30 minutes, 35 minutes or 40 minutes, etc.
[0035] Preferably, the mixing speed in step (3) is 300-500 rpm, such as 300 rpm, 350 rpm, 400 rpm, 450 rpm or 500 rpm, and the mixing time is 20-40 minutes, such as 20 minutes, 25 minutes, 30 minutes, 35 minutes or 40 minutes, etc.
[0036] Preferably, the mixing speed in step (4) is 300-500 rpm, such as 300 rpm, 350 rpm, 400 rpm, 450 rpm or 500 rpm, and the mixing time is 20-40 minutes, such as 20 minutes, 25 minutes, 30 minutes, 35 minutes or 40 minutes, etc.
[0037] Preferably, the mixing speed in step (5) is 300-500 rpm, such as 300 rpm, 350 rpm, 400 rpm, 450 rpm or 500 rpm, and the mixing time is 50-70 minutes, such as 50 minutes, 55 minutes, 60 minutes, 65 minutes or 70 minutes, etc.
[0038] In a third aspect, the present invention provides a UTG-QD plate, wherein the UTG-QD plate comprises a first UTG (Ultra-Thin Glass) sheet, a quantum dot glue layer, and a second UTG sheet which are stacked;
[0039] The quantum dot glue layer is formed by curing the quantum dot glue described in the first aspect.
[0040] Preferably, the thickness of the first UTG sheet and the second UTG sheet are independently 50-90 μm, for example, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm or 90 μm.
[0041] Preferably, the thickness of the quantum dot glue layer is 80-120 μm, for example, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, 105 μm, 110 μm, 115 μm or 120 μm.
[0042] The UTG-QD board (also called a brightness enhancement sheet) provided by the present invention includes two layers of UTG ultra-thin glass sheets and quantum dot glue encapsulated therein. The UTG ultra-thin glass sheets have rigidity, good thermal conductivity and water and oxygen barrier properties. The quantum dot glue encapsulated therein can exert its optical properties and high temperature resistance well, and has a lower cost.
[0043] The present invention does not specifically limit the preparation method of the UTG-QD plate. Exemplarily, the UTG-QD plate can be prepared by the following method:
[0044] A layer of quantum dot glue is evenly coated on the first UTG sheet by a slit coater, and a second UTG sheet is attached on the quantum dot glue layer. After UV light curing and edge sealing, the UTG-QD board is obtained.
[0045] In a fourth aspect, the present invention provides an application of the UTG-QD board as described in the third aspect in the display industry (eg, the automotive display industry).
[0046] Compared with the prior art, the present invention has at least the following beneficial effects:
[0047] (1) In the present invention, the phosphate-containing polymer can be used as a surface ligand to protect quantum dots and increase their stability, and can also be used as an encapsulation material to encapsulate quantum dots; the thiol-containing acrylic monomer is used as a diluent, which has good compatibility with red and green quantum dots and prevents quantum dots from quenching. When the quantum dot glue is used for the UTG-QD board, the light conversion rate of the UTG-QD board can be increased; in addition, the phosphate-containing polymer and thiol-containing acrylic monomer in the quantum dot glue can improve the high temperature stability of the UTG-QD board (after the UTG-QD board is baked at 85°C for 500 hours, the quantum dot LV attenuation rate is still less than 20%).
[0048] (2) The present invention uses UTG sheets to encapsulate quantum dots, so that the UTG-QD board has good optical properties, high temperature resistance, and low cost. DETAILED DESCRIPTION
[0049] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0050] Example 1
[0051] In this embodiment, a quantum dot glue is provided. The raw materials for preparing the quantum dot glue include the following components in parts by weight:
[0052]
[0053] Among them, the phosphate ester polymer is BASF PA9083 resin; the thiol-containing acrylic monomer is 3-mercaptoethyl acrylate; the thermal stabilizer is tricyclodecane dimethanol diacrylate; the photoinitiator is 1-hydroxycyclohexyl phenyl ketone; the light stabilizer is BASF Tinuvin 249; the defoamer is KS Chemical Rheoflow LP-2745; the red quantum dots are CdS / ZnS, and the surface ligand of the red quantum dots is oleic acid; the green quantum dots are CdS / ZnS, and the surface ligand of the red quantum dots is oleic acid.
[0054] The preparation method comprises the following steps:
[0055] (1) firstly adding a thiol-containing acrylic monomer, a heat stabilizer, a photoinitiator, and a light stabilizer into a stirring tank, and stirring at a speed of 300 rpm for 30 minutes at room temperature until the mixture is completely dissolved, to obtain a first mixture;
[0056] (2) adding the phosphate-containing polymer to the first mixture, stirring at room temperature at a rotation speed of 300 rpm for 30 minutes until the mixture is completely dissolved, to obtain a second mixture;
[0057] (3) adding green quantum dots to the second mixture, stirring at room temperature at a rotation speed of 400 rpm for 30 minutes until completely dissolved, to obtain a third mixture;
[0058] (4) adding red quantum dots to the third mixture, stirring at 400 rpm for 30 minutes at room temperature until the red quantum dots are completely dissolved, to obtain a fourth mixture;
[0059] (5) Add titanium dioxide and a defoaming agent to the fourth mixture, and stir at a rotation speed of 400 rpm for 60 minutes at room temperature until the mixture is completely dispersed to obtain the quantum dot glue.
[0060] Example 2
[0061] In this embodiment, a quantum dot glue is provided. The raw materials for preparing the quantum dot glue include the following components in parts by weight:
[0062]
[0063]
[0064] Among them, the phosphate-containing polymer is BASF PA9083 resin; the thiol-containing acrylic monomer is ethylene glycol di(3-mercaptopropionate); the thermal stabilizer is tricyclodecane dimethanol diacrylate; the photoinitiator is 1-hydroxycyclohexyl phenyl ketone; the light stabilizer is BASF Tinuvin 249; the defoamer is KS Chemical Rheoflow LP-2745; the red quantum dots are CdS / ZnS, and the surface ligand of the red quantum dots is octanethiol; the green quantum dots are CdS / ZnS, and the surface ligand of the red quantum dots is octanethiol.
[0065] The preparation method is the same as Example 1.
[0066] Example 3
[0067] In this embodiment, a quantum dot glue is provided. The raw materials for preparing the quantum dot glue include the following components in parts by weight:
[0068]
[0069] Among them, the phosphate ester polymer is BASF PA9083 resin; the thiol-containing acrylic monomer is trimethylolpropane tris(3-mercaptopropionate); the thermal stabilizer is tricyclodecane dimethanol diacrylate; the photoinitiator is 1-hydroxycyclohexyl phenyl ketone; the light stabilizer is BASF Tinuvin 249; the defoamer is KS Chemical Rheoflow LP-2745; the red quantum dots are CdS / ZnS, and the surface ligand of the red quantum dots is oleic acid; the green quantum dots are CdS / ZnS, and the surface ligand of the red quantum dots is oleic acid.
[0070] The preparation method is the same as Example 1.
[0071] Example 4
[0072] In this embodiment, a quantum dot glue is provided. The raw materials for preparing the quantum dot glue include the following components in parts by weight:
[0073]
[0074] Among them, the phosphate-containing polymer is BASF PA9083 resin; the thiol-containing acrylic monomer is pentaerythritol tetrakis (3-mercaptopropionate); the thermal stabilizer is tricyclodecane dimethanol diacrylate; the photoinitiator is 1-hydroxycyclohexyl phenyl ketone; the light stabilizer is BASF Tinuvin 249; the defoamer is KS Chemical Rheoflow LP-2745; the red quantum dots are CdS / ZnS, and the surface ligand of the red quantum dots is oleic acid; the green quantum dots are CdS / ZnS, and the surface ligand of the red quantum dots is oleic acid.
[0075] The preparation method is the same as Example 1.
[0076] Example 5
[0077] The only difference between this embodiment and embodiment 1 is that the phosphate ester polymer is replaced with an equal weight portion of WDS-9051 phosphate ester resin.
[0078] Example 6
[0079] The only difference between this embodiment and embodiment 1 is that the thiol-containing acrylic acid monomer is replaced with an equal weight portion of 3-mercaptoacrylate methyl ester.
[0080] Comparative Example 1
[0081] The only difference between this comparative example and Example 1 is that the weight portion of the phosphoric acid ester polymer is 15 parts.
[0082] Comparative Example 2
[0083] The only difference between this comparative example and Example 1 is that the weight portion of the phosphoric acid ester polymer is 55 parts.
[0084] Comparative Example 3
[0085] The only difference between this comparative example and Example 1 is that the weight portion of the thiol-containing acrylic acid monomer is 5 parts.
[0086] Comparative Example 4
[0087] The only difference between this comparative example and Example 1 is that the weight portion of the thiol-containing acrylic acid monomer is 50 parts.
[0088] Application Examples 1-6 and Comparative Application Examples 1-4
[0089] In Application Examples 1-6 and Comparative Application Examples 1-4, a UTG-QD board is provided respectively, and the UTG-QD board includes a first UTG sheet, a quantum dot glue layer, and a second UTG sheet which are stacked; the quantum dot glue layer is formed by curing the quantum dot glue provided in Examples 1-6 and Comparative Examples 1-4 respectively.
[0090] The thickness of the first UTG sheet and the second UTG sheet are both 70 μm, and the thickness of the quantum dot glue layer is 100 μm.
[0091] The preparation method comprises the following steps:
[0092] A layer of quantum dot glue is evenly coated on the first UTG sheet by a slit coater, and a second UTG sheet is attached on the quantum dot glue layer. After UV light curing and edge sealing, the UTG-QD board is obtained.
[0093] The optical thermal stability test of the brightness enhancement sheet UTG-QD board provided in the corresponding application example 1-6 and the comparative application example 1-4 was carried out. The test conditions were long-term baking at 85°C and then the LV attenuation rate was tested.
[0094] The performance test results are shown in Table 1.
[0095] Table 1
[0096] 0h 120h 240h 500h Application Example 1 0% -8.0% -13.0% -18.0% Application Example 2 0% -1.7% -12.6% -15.3% Application Example 3 0% -2.0% -9.6% -11.4% Application Example 4 0% -1.1% -5.7% -9.3% Application Example 5 0% -15.8% -18.3% -22.1% Application Example 6 0% -10.4% -15.3% -20.7% Comparative application example 1 0% -15.1% -19.4% -23.2% Comparative Application Example 2 0% -7.6% -12.8% -17.1% Comparative Application Example 3 0% -12.0% -18.5 -21.2% Comparative Application Example 4 0% -7.1% -12.1% -16.7%
[0097] In Table 1, the time 0h is the initial quantum dot LV attenuation rate. As the heating time increases, the quantum dot LV attenuation rate of the brightness enhancement sheet UTG-QD plate gradually increases. It can be seen from Table 1 that the quantum dot LV attenuation rate of the brightness enhancement sheet UTG-QD plate prepared by the quantum dot glue provided in Application Examples 1-4 of the present invention remains low after a long period of baking at 85°C (after baking at 85°C for 500h, the quantum dot LV attenuation rate is still less than 20%). For example, after the brightness enhancement sheet UTG-QD plate in Application Example 4 was baked at 85°C for 500 hours, the quantum dot LV attenuation rate was only 9.3%, which means that fewer red and green quantum dots are quenched after the glue and UTG encapsulation.
[0098] Compared with Application Example 1, Application Example 5 replaces the phosphate polymer with an equal weight portion of WDS-9051 phosphate resin. After the prepared UTG-QD board is baked at 85°C, the LV attenuation rate of quantum dots increases significantly. The performance of WDS-9051 phosphate resin in stabilizing quantum dots is not as good as BASF PA9083 resin.
[0099] Compared with Application Example 1, Application Example 6 replaces the thiol-containing acrylic monomer with an equal weight portion of 3-mercaptoacrylate methyl. After the prepared UTG-QD plate is baked at 85°C, the LV attenuation rate of quantum dots increases, and the performance of 3-mercaptoacrylate methyl is not as good as 3-mercaptoacrylate ethyl.
[0100] Compared with Application Example 1, the weight fraction of the phosphate polymer in Application Example 1 is significantly reduced, and after the prepared brightness enhancement sheet UTG-QD plate is baked at 85°C, the quantum dot LV attenuation rate is significantly increased.
[0101] Compared with Application Example 1, the weight portion of the phosphate polymer in Comparative Application Example 2 is increased to 55 parts. After the prepared brightness enhancement sheet UTG-QD plate is baked at 85°C, the quantum dot LV attenuation rate does not change significantly, but it will increase costs and cause waste of raw materials.
[0102] Compared with Application Example 1, the weight fraction of the thiol-containing acrylic monomer in Comparative Application Example 3 is significantly reduced, and after the prepared brightness enhancement sheet UTG-QD plate is baked at 85°C, the quantum dot LV attenuation rate is significantly increased.
[0103] Compared with Application Example 1, in Comparative Application Example 4, the weight fraction of the thiol acrylic monomer is increased to 50. After the prepared brightness enhancement sheet UTG-QD plate is baked at 85°C, the LV attenuation rate of the quantum dots does not change significantly, but it will increase the cost and cause waste of raw materials.
[0104] The applicant declares that the present invention illustrates the quantum dot glue and its preparation method and application through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A quantum dot glue, characterized in that: The raw materials for preparing the quantum dot glue include the following components in parts by weight:
2. The quantum dot glue according to claim 1, characterized in that The phosphate ester polymer includes BASF PA9083 resin and / or WDS-9051 phosphate ester resin; Preferably, the thiol-containing acrylic monomer includes any one or a combination of at least two of methyl 3-mercaptoacrylate, ethyl 3-mercaptoacrylate, ethylene glycol di(3-mercaptopropionate), trimethylolpropane tris(3-mercaptopropionate) or pentaerythritol tetrakis(3-mercaptopropionate).
3. The quantum dot glue according to claim 1 or 2, characterized in that: The heat stabilizer includes tricyclodecane dimethanol diacrylate; Preferably, the photoinitiator comprises 1-hydroxycyclohexyl phenyl ketone.
4. The quantum dot glue according to any one of claims 1 to 3, characterized in that The light stabilizer includes BASF Tinuvin 249; Preferably, the defoaming agent comprises KS Chemical Rheoflow LP-2745.
5. The quantum dot glue according to any one of claims 1 to 4, characterized in that: The red quantum dots are CdS / ZnS, and the surface ligands of the red quantum dots are oleic acid or octanethiol; Preferably, the green quantum dots are CdS / ZnS, and the surface ligands of the red quantum dots are oleic acid or octanethiol.
6. A method for preparing the quantum dot glue as claimed in any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: (1) mixing a thiol-containing acrylic monomer, a heat stabilizer, a photoinitiator, and a light stabilizer to obtain a first mixture; (2) adding the phosphoric acid ester polymer to the first mixture and mixing to obtain a second mixture; (3) adding green quantum dots to the second mixture and mixing to obtain a third mixture; (4) adding red quantum dots to the third mixture and mixing to obtain a fourth mixture; (5) Add titanium dioxide and a defoaming agent to the fourth mixture and mix them to obtain the quantum dot glue.
7. The preparation method according to claim 6, characterized in that: The mixing speed of step (1) is 200-400 rpm, and the mixing time is 20-40 minutes; Preferably, the mixing speed in step (2) is 200-400 rpm, and the mixing time is 20-40 minutes; Preferably, the mixing speed in step (3) is 300-500 rpm, and the mixing time is 20-40 minutes; Preferably, the mixing speed in step (4) is 300-500 rpm, and the mixing time is 20-40 minutes; Preferably, the mixing speed in step (5) is 300-500 rpm, and the mixing time is 50-70 minutes.
8. A UTG-QD board, characterized in that: The UTG-QD plate includes a first UTG sheet, a quantum dot glue layer, and a second UTG sheet that are stacked; The quantum dot glue layer is formed by curing the quantum dot glue according to any one of claims 1 to 5.
9. The UTG-QD board according to claim 8, characterized in that: The thickness of the first UTG sheet and the second UTG sheet are each independently 50-90 μm; Preferably, the thickness of the quantum dot glue layer is 80-120 μm.
10. Application of the UTG-QD board as claimed in claim 8 or 9 in the display industry.